A Study of Asymptomatic UTI Among the Pregnant Women in the Saptari District of Nepal - Chakrabarti, Swapankumar; Mali, Siyaram Bhagat (International Journal For Research In Biology & Pharmacy, 2020)
Urinary tract infection (UTI) is caused by microbial invasion of tissue lining the urinary tract which extends from renal cortex to urethral meatus. Asymptomatic UTI is a significant bacterial count (usually >105 organisms/ml.) present in the urine of persons without any symptom. The present study was conducted to find out the incidence of asymptomatic UTI in pregnant women in the Saptari district of Nepal and to know the antibiotic susceptibility pattern of the isolates. The work was carried out in the Microbiology Laboratory of Tribhuvan University, MBM Campus, Rajbiraj, Nepal during half of the first quarter of 2018 A.D. A total of 100 midstream urine samples of pregnant women from different villages were collected and processed using standard microbiological technique. All the samples were cultured on Blood Agar and McConkey Agar to identify the potential pathogen. To observe colour, odour and turbidity macroscopic observation was done. Microscopic examination was performed to observe pus cell, RBC, epithelial cell, cast and crystal. For the screening of the samples Uristrip analysis was performed. The antibiotic sensitivity test was conducted for the bacteria which grew significantly during culture. The colony count was done and the organisms were identified by biochemical tests. In course of our study asymptomatic bacteriuria was observed in 6% cases. Among the isolates Escherichia coli is found to be the major causative agent. The study also reveals that most of the isolates are resistant to one or more antibiotics.